Digital Media, Language Shift, and Identity Reconstruction: A Sociolinguistic Study among Coastal Youth in the Sunda Strait Area - Hayati Nupus; Ubaidillah; Elda Mnemonica Rosadi (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2026)
While the decline of regional languages due to globalization is well-documented, a significant research gap remains regarding how digital media environments specifically reshape the linguistic ecology and identity negotiation of localized demographic groups. This study examines the influence of digital media on language shift among coastal youth in the Sunda Strait area and its implications for local identity reconstruction. Employing a descriptive qualitative method with a sociolinguistic approach, data were collected through semi-structured interviews, observations, and digital documentation. The study involved six participants, consisting of 3 coastal youth aged 16 and 18 years, along with 2 parents, 1 teacher, The data were analyzed using data condensation, data display, and conclusion drawing. The specific findings reveal a strict domain-based language shift: the active use of the local language is heavily restricted to familial and traditional interactions, whereas Indonesian, digital slang, and English almost entirely dominate peer interactions and digital communicative spaces. Furthermore, the study reveals that local identity among coastal youth is not disappearing but is undergoing a hybrid reconstruction. Youth actively promote local cultural symbols online, yet they articulate these expressions using dominant national and digital languages rather than their local language. This study contributes to the sociolinguistic literature by providing an empirical model of digital language ecology, demonstrating that digital media accelerates language shift by separating cultural visibility from linguistic vitality, thus offering a new perspective on how youth negotiate local belonging within digital networks.